Peningkatan Hasil Belajar Siswa menggunakan Model Pembelajaran Inkuiri Pada Pembelajaran IPA Di Sekolah Dasar - Andini, Fania; Zuryanty, Zuryanty; Rahmatina, Rahmatina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The purpose of this study is to describe improvement of student learning outcomes in science learning using the inquiry learning model. This research is a classroom action research (CAR), using short qualitative and quantitative methods. This study consists of two cycles with observation sheet research instruments test sheet. The research subjects were teachers and six grade students of elementary school 01 Kapau, Agam Regency, amounting to 20 people.The results showed an increase in: (a) Plans in the first cycle were on average 72,5% (B ) cycle II to 87,5%(B), (b) Implementation of cycle I aspect of the teacher averaged 78,7%(C) cycle II to 90% (SB) and cycle implementation The aspect of students with a score of 76,5% (C) cycle II to 87,5%(B) , (c) student learning outcomes in cycle I on average were 75, cycle II to 82,8 (B). Concluded that CTL models can improve science learning outcomes for students of elementary school. Keywords: inquiry learning model, sains